Studying supernova neutrinos through nuclear structure calculations - Tsakstara, V.; Kosmas, T. S.; Sinatkas, J. (HNPS Advances in Nuclear Physics, 2019)
Differential and integrated cross section calculations are performed in the context of the quasi particle random phase approximation (QRPA) by utilizing realistic two- nucleon forces, for the 64,66 Zn isotopes, contents of the COBRA double beta decay detector. For these isotopes the response to supernova neutrinos is of current inter- est. The response of the 66 Zn isotope to the energy-spectra of supernova neutrinos is also explored by convoluting the original results for the differential cross sections by employing: (i) a two-parameter Fermi-Dirac (FD) and (ii) a Power-Law (PL) neutrino energy distribution. Such folded cross sections are useful in low-energy astrophysical-neutrino detection in underground terrestrial experiments.